Estabilidad a largo plazo de Cefabroncol duo tableta recubierta - Ibañez Ahuanari, Erwin Alexander (2018)
The present report of pre-professional practices was to determine the long-term stability of Cefabroncol duo coated tablet in a laboratory of the national pharmaceutical industry. The sample consisted of 3 different lots of 360 tablets each, a simple random sampling was carried out. We proceeded with the description test by visual inspection on a white background and natural light, likewise the uniformity of weight was determined, taking the individual weight of 20 tablets, calculating the average weight. For the dosing and dissolution of the active pharmaceutical ingredients (IFAs), both of Cephalexin and Ambroxol hydrochloride, we proceeded to treat standard and sample according to laboratory analysis technique. The results obtained were: description, coated tablet of oblong shape, with central groove on one side, lilac color. The uniformity of weight is maintained within the range 1240,0 mg / tab. ± 5% (1178,00 - 1302,00) mg / tab, fulfilling the specification for the three lots. For the assay of dosing and dissolution of cephalexin and ambroxol hydrochloride it was demonstrated that the concentration of both active principles in the product does not show significant variability during the 36 months of analysis. It is concluded that the product Cefabroncol duo coated tablet had stability in its characteristics, weight and concentration of active ingredients during the 36 months of evaluation, fulfilling the specifications of the laboratory analysis technique of the pharmaceutical industry